DRAMATIC DISCOURSE AND ITS PRAGMATIC CHARACTERISTICS - Munozat RASULOVA (Scholar Express Journal, 2024)
As the scope of linguistic research expands, the weight of research aimed at analyzing the occurrence of language in different contexts and the cause-and-effect relationship is also increasing. Discourse studies can also be included
Keywords: dramatic; discourse; pragmatic; language